The Impact of the COVID-19 Pandemic on Sexual Behaviors: Findings From a National Survey in the United States. Issue 11 (22nd August 2021) - Gleason, Neil; Banik, Swagata; Braverman, Jesse; Coleman, Eli
ABSTRACT: Background: Studies from the first months of the coronavirus disease 2019 (COVID-19) pandemic and the resulting lockdown and social distancing measures have shown that there have been decreases in sexual frequency and relationship satisfaction. Aim: To evaluate the ongoing impact of the COVID-19 pandemic on sexual behavior, relationship satisfaction, and intimate partner violence in the United States using a large national convenience sample. Methods: About 1, 051 participants across the United States were recruited in October 2020 to complete a cross-sectional online survey. Outcomes: Participants were asked to retrospectively report their sexual behavior frequency, relationship satisfaction, and intimate partner violence during the pandemic and prior to the pandemic RESULTS: There was a small but significant decrease in some retrospectively-reported partnered sexual activities, and men reported a small increase in masturbation and pornography use. There was no evidence for a change in relationship satisfaction or intimate partner violence, but both men and women reported a small decrease in sexual pleasure, and women reported a small decrease in sexual desire. The sexual behaviors with greatest reduction were casual sex, hookups, and number of partners, and the most diminished as aspect of sexual functioning was sexual enjoyment. Depression symptoms, relationship status, and perceived importance of social distancing emerged as predictors of these reductions. Less than half of individuals who engaged with casual sex partners before the start of the pandemic ceased this behavior completely after the start of the pandemic. Individuals waited on average 6–7 weeks before reengaging in casual sex. Clinical Implications: These results inform public health response to the effects of the pandemic and add to our understanding of how the pandemic has continued to impact sexual behavior. Strengths and Limitations: This is the first known study to evaluate sexual behavior several months into the COVID-19 pandemic using a large national sample. However, the results of this study are limited by its convenience sampling method and cross-sectional design. CONCLUSION: These results indicate that the changes in sexual behavior observed in the early months of the pandemic have continued, with small but significant decreases in many partnered sexual behaviors and a small increase in men's solitary sexual behaviors.